Voz e memoria: a correspondencia entre Xoán Vidal Martínez1 e Xosé M.ª Álvarez Blázquez (I) - Acuña, Ana (Madrygal. Revista de Estudios Gallegos, 2005)
This paper witnesses the bonds of frienship between Xoan Vidal Martínez and Xosé María Álvarez Blázquez. Our focus is on the correspondence kept by these two poets through significant periods of their lives.